A first contribution to the validation of the Italian version of the Behavioral Pain Scale in sedated, intubated, and mechanically ventilated paediatric patients - Sulla, Francesco; La Chimia, Melania; Barbieri, Lucrezia; Gigantiello, Antonella; Iraci, Concetta; Virgili, Giulia; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Numerous negative outcomes of inadequate pain management among children have been cited in the literature. Inadequate pain management may be particularly detrimental to children and adolescents facing life-threatening injury or illness on a Paediatric Intensive Care Unit (PICU). It is therefore absolutely necessary that professionals utilize effective and efficient tools in order to evaluate a person’s sensations of pain in the most objective way possible. The COMFORT-B scale is recognised as the gold standard in such patients. However, the use of this instrument in the clinical PICU setting is disputed. It requires long periods of observation to ensure an adequate utilization. Boerlage et al. noted that nurses are often impatient and do not always observe the patient for the recommended 2 minutes period. The Behavioral Pain Scale (BPS), instead, is considered to be the gold standard for pain assessment in deeply sedated, mechanically ventilated adult patients. This observational pain scale requires shorter observation time compared to the COMFORT-B. Moreover, BPS three subscales are included in other observational pain scales for paediatric patients. Therefore, the objective of this study was to assess the applicability of the BPS for use with paediatric patients. Methods: Firstly, a questionnaire was administered to physicians and nursing staff that work in the units where the study was conducted in order to investigate the actual use of observational pain scales in their units. A second questionnaire was administered to a group of experts regarding the BPS, to assess both face validity and content validity, and to gain opinions on the relative appropriateness of each item. A descriptive, comparative design was used. A convenience sample of non-verbal, sedated and mechanically ventilated critical care paediatric patients was included. 39 observations were collected from 9 patients, all in their first year of age. Patient pain was assessed concurrently with the three observational scales, before, during and after routine procedures that are considered painful and non-painful. Results: The data collected through questionnaires for professionals gave a useful insight into pain assessment in the investigated units: only 46% of respondents stated that they assessed patients’ pain levels, with an average of 2.8 times per shift; 60% of respondents declared to be unhappy with the observational scales that they utilise. Regarding the observations, internal consistency was α = .865. Correlations between BPS and the other instruments were high, demonstrating a good concurrent validity of the test. T test and ROC curves demonstrated a good discriminant validity as well. Conclusions: Although the current study is based on a small sample of participants, these first results encourage us to continue working in the validation of the BPS in paediatric patients.